(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2026)
Artificial Wisdom is final future AI or ultimate Artificial Brain at Earth, Space, Intersteller or at Cosmic level wide where all possible Ais interconnected and form one giant AI. Hence itsneed precisemodelling and engineering which I itriedwith simple but deep models the Octane model with 8 Sections, where each section further has 4 layers where each layer further has 3,4 or 5 segments as shown in layer models which applicable on all types of AI simillarly and finally for Artificial Mesh/Brain or AW inter sections and layers as well as intra sections signals and communication engineering require for same type and different types of AIs and with all possible communications shown in last model.